Development of MATLAB GUI-Based Mathematics Learning Media with ADDIE Model to Enhance Students' Mathematical Connection Ability - Putra, Fikri Haykal Kusuma; Taufik, Marhan; Nadlifah, Minatun (Department of Mathematics Education University of Muhammadiyah Malang, 2024)
Research was conducted to develop learning media using Matlab GUI to enhance students' connection abilities. The aim was to create media containing valid, practical, and effective arithmetic and geometric sequences and series to support mathematical understanding. The study involved 10 randomly selected eleventh-grade students. Data was collected from validation results, tests, and student questionnaires. The research followed the ADDIE model in five stages: analysis, design, development, implementation, and evaluation. Media validation test results showed 86.5% validity, while student use scored 85.67% for practicality. Effectiveness testing revealed an average student score of 85.84%, demonstrating high effectiveness. These findings indicate that the Matlab GUI-based learning media successfully meet valid, effective, and practical criteria for enhancing students' mathematical connection abilities.